AUGMENTED REALITY AS AN INNOVATIVE LEARNING MEDIA FOR VERTEBRATE ANIMALS FOR ELEMENTARY SCHOOL STUDENTS - Fikri Akbar Syah Putra Nasution; Imran Lubis (Ninety Media Publisher, 2026)
The learning of vertebrate animals in elementary schools often faces challenges due to the limited availability of interactive media, resulting in reduced understanding and low student motivation. This study aims to design and implement an Augmented Reality (AR) application as an innovative learning medium capable of displaying 3D models of vertebrate animals in an interactive and realistic manner. The application was developed using Unity 3D and Vuforia SDK, with key features including AR Camera, Materials, Guide, Download Marker, and About. The learning materials cover various vertebrate categories such as fish, frogs, birds, lions, and elephants, with detailed information on their characteristics, behaviors, and classification. User testing demonstrated that the application runs smoothly on Android devices and successfully increases student engagement, motivation, and understanding of biological concepts. The integration of AR technology allows students to visualize animals directly in three-dimensional space, providing a more immersive and enjoyable learning experience compared to conventional methods. Additionally, the application overcomes the limitations of physical models or field visits, offering accessible and flexible learning within the classroom. The results indicate that AR can serve as an effective educational tool, enhancing both the quality and interactivity of biology learning. This study contributes to the development of technology-based learning methods in elementary education and demonstrates the potential of AR to improve students’ cognitive and perceptual understanding of vertebrate animals.